Safety and efficacy of biologic immunosuppressive treatment in juvenile idiopathic arthritis associated with inborn errors of immunity - Accardo, V.; Pagnini, I.; Maccora, I.; Marrani, E.; Mastrolia, M. V.; Simonini, G. (Frontiers in Pediatrics, 2024)
Objectives This study aims to describe clinical features, therapeutic outcomes, and safety profiles in patients affected by juvenile idiopathic arthritis (JIA) and inborn errors of immunity (IEI) treated with biological Disease-modifying antirheumatic drugs (DMARDs). Methods We enrolled three patients who were followed in the Pediatric Rheumatology Unit at Meyer Children's Hospital in Florence; these patients were affected by JIA, according to ILAR criteria, and IEI, according to the IUIS Phenotypical Classification for Human Inborn Errors of Immunity. Among them, two patients had 22q11.2 deletion syndrome (22q11.2DS) and one patient had X-linked agammaglobulinemia (XLA). Results Case 1: A 6-year and 2-month-old boy was affected by 22q11.2DS, associated with oligoarticular JIA, at the age of 2 years. He was treated with non-steroidal anti-inflammatory drugs (NSAIDs) and methotrexate, along with oral glucocorticoids but with no benefits. Treatment with etanercept allowed him to achieve remission after 10 months. Case 2: A 6-year and 2-month-old girl was affected by 22q11.2DS, associated with oligoarticular JIA, at the age of 3 years and 11 months. She was treated with NSAIDs, joint injections, and methotrexate but without clinical response. Treatment with Adalimumab allowed her to achieve remission after 6 months. Case 3: A 12-year and 2-month-old boy was affected by XLA, associated with polyarticular JIA, at the age of 9 years and 11 months. He was treated with NSAIDs, methotrexate, joint injections, and oral glucocorticoids with no benefits. He failed to respond to anti-TNF-alpha, tocilizumab, and abatacept. Currently, he is undergoing therapy with sirolimus plus abatacept, which allowed him to achieve remission after 4 months. Conclusions Results suggest that the use of immunosuppressive biological therapies can control disease activity in these patients. No adverse drug-related reactions were observed during the follow-up.